Mapping and Characterization of a Wheat Stem Rust Resistance Gene in Durum Wheat “Kronos” - Li, Hongna; Hua, Lei; Rouse, Matthew N.; Li, Tianya; Pang, Shuyong; Bai, Shengsheng; Shen, Tao; Luo, Jing; Li, Hongyu; Zhang, Wenjun; Wang, Xiaodong; Dubcovsky, Jorge; et al. (Frontiers in Plant Science, 2021)
Wheat stem (or black) rust is one of the most devastating fungal diseases, threatening global wheat production. Identification, mapping and deployment of effective resistance genes are critical to address this challenge. In this study, we mapped and characterized one stem rust resistance (Sr) gene from the tetraploid durum wheat variety Kronos (temporary designation SrKN). This gene was mapped on the long arm of chromosome 2B and conferred resistance to multiple virulent Pgt races such as TRTTF and BCCBC. Using a large mapping population (3,366 gametes), we mapped SrKN within a 0.29 cM region flanked by sequenced-based markers pku4856F2R2 and pku4917F3R3, which corresponds to 5.6-Mb and 7.2-Mb regions in the Svevo and Chinese Spring reference genomes, respectively. Both regions include a cluster of nucleotide binding leucine-repeat (NLR) genes that represent potential candidate genes. An allelism test failed to detect recombination between SrKN and the previously mapped Sr9e gene. This result, together with similar seedling resistance responses and resistance profiles, suggested that SrKN and Sr9e may represent the same gene. We introgressed SrKN into common wheat, and developed completely linked markers to accelerate its deployment in wheat breeding programs. SrKN can be a valuable component of transgenic cassettes or gene pyramids including multiple resistance genes to control this devastating disease.